2014
DOI: 10.2217/imt.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Irradiated Mononuclear Cells Express Significant In Vitro Cytotoxic Activity: Promise for In Vivo Clinical Efficacy of Irradiated Mismatched Donor Lymphocytes Infusion

Abstract: The efficacy of irradiated haploidentical lymphocytes should be further tested in a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Cells were infused after day þ30 (avoiding antithymocyte globulin toxicity) and although, the results might deserve further study, immune recovery was observed. Ideas are not scarce and other novel pDLI approaches are being reported, including mononuclear cell irradiation [97] and a phase II trial of infusion preemptive T-cell rapamycin resistant at day þ14 after allo-HCT [98].…”
Section: In Extramedullary Relapsesmentioning
confidence: 99%
“…Cells were infused after day þ30 (avoiding antithymocyte globulin toxicity) and although, the results might deserve further study, immune recovery was observed. Ideas are not scarce and other novel pDLI approaches are being reported, including mononuclear cell irradiation [97] and a phase II trial of infusion preemptive T-cell rapamycin resistant at day þ14 after allo-HCT [98].…”
Section: In Extramedullary Relapsesmentioning
confidence: 99%
“…Lymphocytes do not perish immediately following irradiation; hence, there is no sustained GVHD with a rising proliferation inhibition rate (9,11,12). As a result, the transfusion of irradiated PBMCs has been performed in certain clinical applications for over a decade (9,11,12,25,26). The aim of the present study was to confirm the optimum dose of X-rays, under appropriate conditions, that can reduce the proliferation of lymphocytes while preserving or enhancing their cytotoxic activity, therefore improving the effectiveness of irradiation in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…К недостаткам данной линии клеток можно отнести тот факт, что они должны быть облучены перед трансфузией, т. к. происходят из линии опухолевых клеток и несут множество генетических аномалий [30]. Многочисленные исследования показали, что клетки NK-92 сохраняют свою цитотоксичность после облучения, но отсутствие пролиферации in vivo приводит к исчезновению введённых клеток уже через 7 дней [31][32][33]. Следовательно, лечение препаратом CAR на основе NK-92, скорее всего, потребует нескольких циклов трансфузии [32].…”
Section: источники Car Nk-клетокunclassified